Long-Noncoding RNA MANCR is Associated With Head and Neck Squamous Cell Carcinoma Malignant Development and Immune Infiltration - Tang, Jianfei; Bao, Mingyan; Chen, Juan; Bin, Xin; Xu, Xinghuanyu; Fang, Xiaodan; Tang, Zhangui (Frontiers in Genetics, 2022)
Recent studies have demonstrated an important role for mitotically associated long non-coding RNA (MANCR) in carcinogenesis and cancer progression, but its function has not been elucidated in head and neck squamous cell carcinoma (HNSCC). In this study, we identified differentially expressed MANCR from The Cancer Genome Atlas (TCGA) and Genotype-Tissue Expression (GTEx) databases across 24 cancer types and included 546 HNSCC patients. Furthermore, high expression of MANCR was verified in HNSCC cell lines and tissue by using real-time quantitative PCR (RT-qPCR) analysis. The Kaplan–Meier analysis showed a worse prognosis with higher levels of MANCR for HNSCC. The univariate Cox regression and multivariate Cox regression analyses revealed that MANCR was a high-risk factor in patients with HNSCC. Thereafter, we carried out the Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses. It was indicated that MANCR participates in axonogenesis and ECM-receptor interaction. Further enrichment analysis demonstrated that the expression of MANCR was positively correlated with the T gamma delta (tgd) cells, neutrophils, and Th1 cells, and negatively correlated with the infiltration of B cells, CD8 T cells, and T cells in HNSCC. In addition, in vitro experiments showed that knockdown of MANCR in HNSCC cells markedly inhibited cell proliferation, migration, and invasion. We find that MANCR was elevated in HNSCC and promoted the malignant progression of HNSCC. MANCR may serve as a potential biomarker in prognostic implications for HNSCC patients. The positive correlation between MANCR and immune infiltration cells may provide novel therapeutic targets and personalized immune-based cancer therapy for HNSCC.